Doctor's role in determining wounds qualification of terrorism victims - Indrayana, Mohammad Tegar; Ulfa, Annisa; Ridwan, Nurul Afrilla; Afikah, Auni; Khasanah, Anytia Zulfa (Atma Jaya Catholic University of Indonesia, 2023)
Introduction: The terms terrorist (perpetrator) and terrorism (action) are derived from the Latin word “terrere” which means to shake or vibrate. The European Convention first discussed the definition of terrorism on the Suppression of Terrorism (ECST) in Europe in 1977; there was a paradigm expansion in the meaning of Crime against State to Crime against Humanity. Crime against Humanity includes criminal acts committed to create a situation that causes individuals, groups, and the general public to be in a tense atmosphere. Necessary to have a clinical forensic examination to determine the degree of injury suffered by victims of terrorist criminal acts as a reference for providing compensation from the state. Case Report: On Friday, October 23rd, 2020, at 09.25 a.m. at the Bhayangkara Hospital Emergency Installation, examinations were conducted on 4 men. The basis for the examination is based on a written request from the LPSK with the number: R-1176/1a.5.1/LPSK/10/2020 on October 21st, 2020. Discussion: There is a mechanism in the forensic examination for the victims of terrorism crimes. The process for obtaining compensation can be submitted by victims of terrorism crimes, their families, or their heirs. LPSK will conduct a substantive examination and calculate the losses suffered by victims of terrorism crimes. Conclusion: Regarding the provisions of these laws and regulations, the Indonesian Forensic Doctors Association (PDFI) cooperates with LPSK, as stated in the cooperation agreement. Key Words: doctor’s role, wound qualification, terrorism victims.